Effect of plant density on growth and yield in Barraganete plantain (Musa paradisiaca (L.) AAB cv. Curare enano) for a single harvest cutting in Provincia de Los Ríos, Ecuador (2017)
The optimum plant density in Barraganete plantain (Musa paradisiaca (L.) AAB cv. Curare enano) was determined in Los Angeles-Provincia de Los Ríos, Ecuador. Treatments (sowing distance: T1 = 3m x 4m, T2 = 3m x 3m, T3 = 3m x 2m, T4 = 3m x 1.5m and T5 = 3m x 1m), were evaluated in a randomized complete block design with five treatments and three replicates per treatment. The number of hands per cluster, hand weight, weeks to flowering, weeks to harvest, production for export and weed incidence in plantain crop, were evaluated. Variance analysis was performed and means were submitted to the Tukey test at 5% probability (p = 0.05). The optimum sowing distance was 2m between plants and 3m between rows. The best density was 1666 plants. ha-1 and obtained the best average hand weight (14.5 kg), the best average number of hands (4.9), the best average in weeks to harvest after flowering (12.1 Weeks) and the best production (kg.ha-1) of export bunches (close to 22 t.ha-1). Analysis with logistic models show the higher densities, which present advantages in their use, fact related to the increase of the annual plantain production. For this reason, values between 2150 and 2500 plants.ha-1 are postulated as optimal densities. Weed decreases with increasing plant density to a minimum of 227.94 g.m-2 in the highest plant density treatment.